IMPLEMNTASI HUKUM ADAT DAN HUKUM NASIONAL DALAM KASUS KEKERASAN SEKSUAL TERHADAP ANAK DI KABUPATEN BIMA - Nurmayana, Suri; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: The sexual violence case involving a religious teacher in Bima Regency, who abused 10 of his students, including his nephew, reveals serious challenges in law enforcement in Indonesia. Based on the Child Protection Law and the Criminal Code, perpetrators can be sentenced to prison terms ranging from 5 to 20 years, depending on the severity of the act. The problem is how is the implementation of Maja Labo Dahu customary law in optimizing the synergy between customary law and national law in protecting children from sexual violence in Bima Regency? How effective is the implementation of national law, especially the Child Protection Law, in handling cases of sexual violence against children in Bima Regency? This study uses a descriptive normative legal research type. Data analysis is qualitative. Conclusions are drawn using deductive logic. The study results show that although there is a clear legal framework, challenges such as social stigma against victims and lack of legal awareness in the community hinder the effectiveness of law enforcement. This situation shows that although laws exist to protect children, social and cultural factors often hamper their implementation. This case also emphasizes the important role of the community and child protection institutions in creating a safe environment for children. A comprehensive approach, which integrates consistent law enforcement and social support for victims, is essential to prevent similar incidents from happening again and ensure justice for children who are victims of sexual violence. Thus, there needs to be a collaborative effort to increase legal awareness and create a more effective child protection system.Keywords: Sexual violence, child protection, social stigma, law enforcement, Bima Regency.